Breakeven Point Analysis of Beef Cattle Business: A Case Study in Boliyohuto Subdistrict, Gorontalo - Singgili, Haris; Aisyah R, St.; Arwati, Sitti (Tarjih : Agribusiness Development Journal, 2024)
Beef cattle farming is important in providing food, especially animal protein, and supporting the community economy. This study illustrates how this livestock business can quickly breakeven point (BEP), cover costs, and start making a profit. The uniqueness of this study lies in the specific analysis of costs, revenues, and income, as well as the calculation of BEP, which can be used as a guideline for more efficient business management. This study aims to analyze the BEP of the beef cattle business in the Boliyohuto District. The sample used was 89 beef cattle farmers using a quantitative approach. Data was collected through observation, interview, and documentation, followed by quantitative descriptive analysis. The results showed that the average total cost incurred was IDR 11,418,410, and revenue was IDR. 19,814,935, income was IDR. 8,396,525. In addition, the breakeven point (BEP) in quantity is 0.576, and the rupiah value is IDR. 5,709,205. The beef cattle business in the Boliyohuto Subdistrict provides economic benefits because the production and unit price is greater than the breakeven point value, so the business is up-and-coming. This research is very relevant in the context of community economic empowerment because the beef cattle sector has the potential to be a stable source of income, support food security, and create jobs. In addition, the results of this study can be the basis for developing policies and programs that support the sustainability of livestock businesses in rural areas, as well as optimizing the profitability of livestock businesses in the long term.